Development and Performance Evaluation of an Okra Slicer. - Ishola, T. A.; Adewole, L. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The traditional method of slicing okra with kitchen knife is labourious, time-consuming and also prone to finger injury. Both traditional method and existing mechanized okra slicer result in damaged and unequal slices of okra which may hinder proper drying of the okra for preservation. An okra slicer was designed, constructed and evaluated. The main parts of the machine were cutting discs, guided removable tray, loading hopper, the transmission system and the supporting frame. In the evaluation of the machine with okra, the performance indices investigated were slicing efficiency, throughput capacity, mechanical damage index and slicing uniformity. The highest slicing efficiency and throughput capacity for okra were 99.88 % and 194.11 kg/h respectively. The least mechanical damage index value of 0.30 % was obtained at a cutting speed of 1200 rpm. The mean slicing uniformity was 93.87 %. The machine developed in this study was able to produce uniform slices of okra of about 3.4 mm thickness. Hence, Industrial production and shelf life of dried okra could be enhanced.